Belatacept Conversion in an HIV‐Positive Kidney Transplant Recipient With Prolonged Delayed Graft Function. Issue 11 (18th July 2016) - Ebcioglu, Z.; Liu, C.; Shapiro, R.; Rana, M.; Salem, F.; Florman, S.; Huprikar, S.; Nair, V.
Abstract : We report an HIV‐positive renal transplant recipient with delayed graft function who was converted from tacrolimus to belatacept in an attempt to improve renal function. The patient had kidney biopsies at 4 and 8 weeks posttransplant that revealed acute tubular necrosis and mild fibrosis. After 14 weeks of delayed function, belatacept was initiated and tacrolimus was weaned off. Shortly after discontinuing tacrolimus, renal function began to improve. The patient was able to discontinue dialysis 21 weeks posttransplant. HIV viral load was undetectable at last follow‐up. To our knowledge, this is the first report of belatacept use in a patient with HIV. Abstract : The authors describe the first successful use of belatacept to improve renal function in a kidney transplant recipient with HIV.